Polygenic adaptation and negative selection across traits, years and environments in a long‐lived plant species (Pinus pinaster Ait., Pinaceae). Issue 7 (15th February 2022) - de Miguel, Marina; Rodríguez‐Quilón, Isabel; Heuertz, Myriam; Hurel, Agathe; Grivet, Delphine; Jaramillo‐Correa, Juan Pablo; Vendramin, Giovanni G.; Plomion, Christophe; Majada, Juan; Alía, Ricardo; Eckert, Andrew J.; González‐Martínez, Santiago C.
Abstract: A decade of genetic association studies in multiple organisms suggests that most complex traits are polygenic; that is, they have a genetic architecture determined by numerous loci, each with small effect‐size. Thus, determining the degree of polygenicity and its variation across traits, environments and time is crucial to understand the genetic basis of phenotypic variation. We applied multilocus approaches to estimate the degree of polygenicity of fitness‐related traits in a long‐lived plant ( Pinus pinaster Ait., maritime pine) and to analyse this variation across environments and years. We evaluated five categories of fitness‐related traits (survival, height, phenology, functional, and biotic‐stress response) in a clonal common‐garden network planted in contrasted environments (over 20, 500 trees). Most of the analysed traits showed evidence of local adaptation based on Q st – F st comparisons. We further observed a remarkably stable degree of polygenicity, averaging 6% (range of 0%–27%), across traits, environments and years. We detected evidence of negative selection, which could explain, at least partially, the high degree of polygenicity. Because polygenic adaptation can occur rapidly, our results suggest that current predictions on the capacity of natural forest tree populations to adapt to new environments should be revised, especially in the current context of climate change.